THE ROLE OF BOARD DIVERSITY IN ENHANCING FINANCIAL PERFORMANCE: EVIDENCE FROM INDONESIAN BANKING INDUSTRY - Yesi Anggraini (GREET, 2025)
This study examines the impact of board diversity on the financial performance of banks in Indonesia, highlighting the role of gender, ethnicity, and professional experience in strengthening governance and organizational outcomes. Using panel data from 30 publicly listed banks over the period 2018–2023, the analysis applies correlation and multiple regression models with financial performance indicators measured by return on assets (ROA) and return on equity (ROE). The results reveal a significant positive association between board diversity and financial performance, suggesting that banks with more heterogeneous boards achieve higher profitability and improved resilience. Specifically, gender diversity and ethnic representation demonstrate robust effects on both ROA and ROE, while professional background enhances decision-making efficiency. These findings are consistent with the resource-based view, which emphasizes diverse boards as valuable strategic assets that enhance innovation, reduce risk, and improve stakeholder trust. The study contributes to the literature by providing empirical evidence from an emerging market context, where research on board diversity remains limited. Practical implications are offered for regulators and policymakers in Indonesia to strengthen diversity-related governance policies, while banks are encouraged to implement inclusive recruitment strategies to optimize financial outcomes.